The Relevance Of Therapeutic Communication In The Book Of á¹¢aá¸¥iá¸¥ Al-Bukhará¿‘ And á¹¢aá¸¥iá¸¥ Muslim In Contemporary Life : Islamic Education Perspective - Sabaruddin S; Nawir Yuslem; Zainun Zainun (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Therapeutic communication is deliberate interaction between therapists and clients for recovery.The author wishes to learn more aboutÂ hadiths from Saá¸¥iá¸¥ al-BukhÄrÄ« and Saá¸¥iá¸¥ Muslim to understand more about therapeutic communication.This research is a type of library research.Â Â This research uses Saá¸¥iá¸¥ al-BukhÄrÄ« and Saá¸¥iá¸¥ Muslim's writings, syará¸¥ books (explanations), journals, and all therapeutic communication material as references. This study employed descriptive technique. This research does not use human data sources. Instead, researchers gather, identify, evaluate, and synthesize data to assess the policy notion of directly or indirectly witnessed occurrences.Therapeutic communication writings in the hadith books of al-Bukhar and Muslim focus on the patient. Encouragement, good service, and a good environment are important. Thirty communication-related hadiths were found in al-Bukhar and Muslim.